Nature and significance of the late Mesozoic granitoids in the southern Great Xing'an range, eastern Central Asian Orogenic Belt. Issue 5 (24th March 2019) - Wan, Le; Lu, Chengdong; Zeng, Zuoxun; Mohammed, Adil S; Liu, Zhenghong; Dai, Qingqin; Chen, Kangli
ABSTRACT: Abundant late Mesozoic granitic rocks are widespread in the southern Great Xing'an Range (GXAR), which have attracted much attention due to its significance for the Mesozoic tectonic evolution in the eastern Central Asian Orogenic Belt. However, controversy has still surrounded the late Mesozoic geodynamic switching in the continental margin of east China, especially the spatial and temporal extent of the influence of the Mongol-Okhotsk and Palaeo-Pacific tectonic regimes. In order to better understand the Late Mesozoic evolutionary history of the southern GXAR, a number of geochemical, geochronological, and isotopic data of the granitoids in this region are collected. Magmatism in the southern GXAR can be divided into six phases: Late Carboniferous (325–303 Ma), Early-Middle Permian (287–260 Ma), Triassic (252–220 Ma), Early Jurassic (182–176 Ma), Late Jurassic (154–146 Ma), and Early Cretaceous (145–111 Ma). Mesozoic magmatic activities in the southern GXAR peaked during the Late Jurassic to Early Cretaceous, accompanied by large-scale mineralization. Sr–Nd–Hf isotopic evidence of these granitic rocks suggested they were likely originated from a mixed source composed of lower crust and newly underplated basaltic crust. Assimilation-fractional crystallization (AFC) or crustal contamination possibly occurred in the magma evolution, and a much more addition of juvenile component to the source of the Early Cretaceous granitoids than that of Late Jurassic. The closure of Mongol-Okhotsk ocean and the break-off of the Mongol-Okhotsk oceanic slab at depth in the Jurassic triggered extensive magmatism and related mineralization in this region. The Jurassic intrusive activities was affected by both the subduction of the Palaeo-Pacific plate and the closure of Mongol-Okhotsk ocean. Less influence of the Mongol-Okhotsk tectonic regime on the Early Cretaceous magmatism, whereas, in contrast the Palaeo-Pacific tectonic regime possibly continued into the Cenozoic.